Frequency of Alpha-Globin Deletions and BCL11A/Xmn-1-HBG2 Polymorphisms Among β-Thalassemia Patients in Pakistan - Tauqeer Ahmad, Fareeda Islam, Nuzhat Firdous, Saleem Adil (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
b-thalassemia remains one of the most common hereditary blood disorders in Pakistan,characterized by marked genetic and phenotypic heterogeneity. This study aimed to determine thefrequency of